Exploration Of Injury Knowledge Levels, Prevention And First Aid For Climbing Athletes - Ilham Ilham; Nuridin Widya Pranoto; Japhet Ndayisenga (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2023)
Objective. The aim of this study was to determine the level of knowledge of climbing athletes regarding injury awareness, prevention and first aid specifically in climbing. In the process of exploration, the level of knowledge includes various methods and concepts, such as how well does the athlete know about injuries, types of injuries, and assistance when and what treatment should be given. Method. This type of research is quantitative research with a quantitative descriptive design. The population taken was students of rock-climbing athletes who love nature and the environment, Padang State University (MPALH UNP). Non-random sampling was done to obtain n=20 participants, consisting of 65% (male) and 35% (female) which included three climbing category numbers, namely lead climbing (LC), speed climbing (SC) and bouldering climbing. (BC). Results. Knowledge of injuries, prevention and assistance in the sport of climbing by MPALH UNP with a score of 48.45 ± 8.4 was found to be in the fairly good category. “Good” score value category n = 1 (5%). “fairly good” category n=15 (75%). Then the score for the "Not good" category n = 4 (20%). Conclusion. The results of this study indicate that the level of knowledge of MPALH UNP climbing athletes on knowledge, prevention and first aid is still in the goodn enough category, although some athletes score in the poor category. Thus, specific training must be provided by the management and the climbing division of the UNP MPALH so that they can improve their capacities in terms of injuries, prevention and first aid to perform.